2019
DOI: 10.1080/21681376.2019.1578259
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the strategic ‘black hole’ in regional innovation coalitions: reflections from the Twente region, eastern Netherlands

Abstract: Active coalitions of regional stakeholders are at the heart of contemporary regional economic development policies, such as Smart Specialisation or Constructing Regional Advantage. These coalitions consist of actors from various organizations such as regional authorities, companies and higher education institutions that come together to achieve common agendas and advance their region. Accordingly, the numerous stakeholders are expected to work together seamlessly, build and implement strategies and thereby del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
(15 reference statements)
1
11
0
1
Order By: Relevance
“…In terms of policy recommendations, different aspects must be considered. Firstly, regional partners need to know how to work together – without being restrained by their institutional differences (Nieth, 2019) – so that the regional strategy processes are effectively about regional development and not (just) about different stakeholders learning to cooperate while “[breaking] down silos between various administrative bodies and improve multi-level governance” (European Commission, 2017: 5). Finally, expectations towards the contribution of universities to regional governance processes are often not aligned with universities’ capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of policy recommendations, different aspects must be considered. Firstly, regional partners need to know how to work together – without being restrained by their institutional differences (Nieth, 2019) – so that the regional strategy processes are effectively about regional development and not (just) about different stakeholders learning to cooperate while “[breaking] down silos between various administrative bodies and improve multi-level governance” (European Commission, 2017: 5). Finally, expectations towards the contribution of universities to regional governance processes are often not aligned with universities’ capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In their study on universities’ contribution to RIS3, Elena-Perez, Arregui Pabollet, and Marinelli (2017) found that universities’ engagement largely depends on a diverse set of regional configurations and instruments that originate different dynamics. Similarly, internal institutional characteristics – such as universities’ disciplinary focus, interface bodies, academic communities, individual agency and leadership potential (Fonseca et al, 2021; Nieth, 2019; Raagmaa and Keerberg, 2017; Thune et al, 2016) – can greatly influence the type of regional roles they assume. Therefore, different types of universities inserted in distinct regional contexts inevitably undertake heterogeneous roles and engagement activities in the regional strategy process.…”
Section: Introductionmentioning
confidence: 99%
“…When dealing with economic and structural transformation processes, it can, for instance, encourage new partnerships between economic and political actors or produce a juxtaposition of these groups. Apart from actor inclusion, the possibility of exclusion of actors also exists, if strategic aims are not shared and tensions arise (Nieth, ). Furthermore, entrepreneurial individuals on the local and regional level can achieve the vertical expansion of the actor spectrum based on personal contacts and networks to superior levels (Miörner & Trippl, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some locally engaged universities are known for having helped their regions develop new innovation capacity. Nieth (2019) studied coalitions of government, industry, and higher education institutions aiming to promote long-term regional change. She found that these coalitions suffered from sub-optimality due to the short-term interests of the individual actors.…”
Section: Universities In Innovation Ecosystemsmentioning
confidence: 99%